Ethnomedicine and Tribal Healing Practices in India Challenges and Possibilities of Recognition and Integration - Reddy, Sunita; Guite, Nemthianngai; Subedi, Bamdev (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book examines various aspects of ethnomedicine and tribal healing practices, including its importance for inclusion and integration from a health systems perspective. Tribal healing practices is an under-studied component in healthcare system, health policy and health systems research. The book consists of original research papers based on empirical studies done by anthropologists, sociologists, public health practitioners and research scientists in various parts of India. It discusses issues of non-codified folk healing, with a focus on the therapeutic ideas and practices of tribal communities, located in anthropological theory and methods. It has a balance of empirical papers, review and theoretical papers, not only explaining 'what is inside the healing practices' but also touching upon the question of 'why' and delving into 'what should be' looking into the possibility to apply it for a larger good i.e., health care for all. This book discusses several important issues related to legitimacy, evidence and efficacy, recognition, certification and integration, protection and preservation, bio-piracy and bioprospecting, benefit sharing and intellectual property rights, sustainable use of medicinal herbs and conservation of nature and natural resources, biodiversity and possibilities of mainstreaming tribal healing. It is of interest to students and researchers from medical anthropology, medical sociology, cultural geography, liberal studies, tribal studies, ecology, sustainability and development and public health.
Introduction: Ethnomedicine and Indigenous Healing Practices among the Tribes of India: Challenges and Possibilities of Integration -- Practices and Praxis: A Critical Look at Medical Anthropology in India -- Ethnomedicine as Public Health -- Biological Diversity Act 2002, An Implementation Challenge In India: An Experience Sharing From Sikkim -- Chronicles Of Exploitation: Practice And Practitioners Of Ethnomedicine In The Quagmire Of Market Dynamics Of Pharmacopeia -- Indigenous Healing Practices in the Himalaya: Use of Medicinal Plants and Health Development in Nepal -- The Folk Healing Practices of the North East States -- Understanding Etiology of Diseases: Special Reference to Lepcha Communities of Dzongu, Sikkim -- Language and Traditional Healing Practice: A Study of Limbu Community.-The nongai dawai Khasi healers of Meghalaya -- Amchi system in Ladakh: Challenges in the New World -- Health Care Systems among Broq-Pa Tribe -- Ethnomedicine in Question: The Case of Tharu Healers and Healing Practices -- Ethics, Morality and Healing: A Bhil Perspective.
Keywords: Medical anthropology; Social medicine; Medical Anthropology; Medical Sociology